Comparative studies on the genetic, antigenic and pathogenic characteristics of Bokeloh bat lyssavirus ... - Nolden, Tobias; Banyard, Ashley C.; Finke, Stefan; Fooks, Anthony R.; Hanke, Dennis; Höper, Dirk; Horton, Daniel L.; Mettenleiter, Thomas C.; Müller, Thomas; Teifke, Jens P.; Freuling, Conrad M. (Zenodo, 2014)
(Uploaded by Plazi for the Bat Literature Project) Bokeloh bat lyssavirus (BBLV), a novel lyssavirus, was isolated from a Natterer's bat ( Myotis nattererii ), a chiropteran species with a widespread and abundant distribution across Europe. As a novel lyssavirus, the risks of BBLV to animal and human health are unknown and as such characterization both in vitro and in vivo was required to assess pathogenicity and vaccine protection. Full genome sequence analysis and antigenic cartography demonstrated that the German BBLV isolates are most closely related to European bat lyssavirus type 2 (EBLV-2) and Khujand virus and can be characterized within phylogroup I. In vivo characterization demonstrated that BBLV was pathogenic in mice when inoculated peripherally causing clinical signs typical for rabies encephalitis, with higher pathogenicity observed in juvenile mice. A limited vaccination-challenge experiment in mice was conducted and suggested that current vaccines would afford some protection against BBLV ...